Plagiarism as a social contract, a new way to approach plagiarism - Gregory, Jess L. (Journal of Academic Ethics, 2021)
Most cases of plagiarism involve a power differential where not every person has the same ability to enter into a social contract. A social contract requires that each party understands the expectations or norms of the contract, has a voice in setting or changing the norms and has the ability to exit the contract. If those with less power want to gain power then they have to engage in activities bound by norms set by others with little or no ability to exit and no voice. Even if one determines that it is an option to choose a role that requires academic writing, even at the earliest grades, then the social contract demands a shared norm of what constitutes correct behavior. This study reviewed the abstracts of articles indexed in Google Scholar from 1999–2019 through the lens of integrative social contract theory (ISCT) and found, in the case of plagiarism, an existing consensus of correct behavior does not exist. Recommendations for establishing a social contract conclude the article.
3 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103650269
Keywords: dept.edl; peer-reviewed